2020
DOI: 10.1103/physrevmaterials.4.015602
|View full text |Cite
|
Sign up to set email alerts
|

Molecular anisotropy and rearrangement as mechanisms of toughness and extensibility in entangled physical gels

Abstract: Dynamic networks formed by physically crosslinked, entangled polymers have emerged as self-healing, stretchable, and functional materials. Entangled associative gels with remarkable toughness and extensibility have been produced by several distinct chemical approaches, suggesting that these enhanced mechanical properties result from molecular-scale topology. Previously, artificially engineered associative proteins were designed to provide an ideal model system to investigate the role of entanglement on gel mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 105 publications
(241 reference statements)
0
24
0
Order By: Relevance
“…As these clusters are densely packed, moving one component would require moving many other components as well. Based on these observations, we hypothesized that branches are entangled, in a manner reminiscent of physical gels (30) and entangled granular materials (31). Entanglement would provide a mechanism for branches of cells to remain in the same, densely packed group even after cell-cell bonds break.…”
Section: Figure 2 Evolution Of Novel Cell Morphology (A)mentioning
confidence: 99%
“…As these clusters are densely packed, moving one component would require moving many other components as well. Based on these observations, we hypothesized that branches are entangled, in a manner reminiscent of physical gels (30) and entangled granular materials (31). Entanglement would provide a mechanism for branches of cells to remain in the same, densely packed group even after cell-cell bonds break.…”
Section: Figure 2 Evolution Of Novel Cell Morphology (A)mentioning
confidence: 99%
“…The Deborah number ( De ) is defined as , which represents a ratio of the time scales of interest (τ R or τ S ) and the time scale of the applied strain rate of our fiSER experiments. 57 When both the bulk relaxation and recovery time scales are nondimensionalized and plotted against the extensional strain to break, a clear trend emerges with the bulk relaxation time ( Figures 7 and S15 ), suggesting that the faster relaxation dynamics of PNP hydrogels comprising more hydrophobic NPs play a role in increasing the extensibility of these materials at these time scales. While the bulk relaxation time scale trends with extensibility, it is possible that structural changes arising from incorporation of the modified NPs may occur that also affect the extensibility.…”
Section: Resultsmentioning
confidence: 98%
“…It is important to note that these materials are formulated with 93% water content, which is significantly higher than previously published physically cross-linked hydrogel materials exhibiting high extensibility. 8 , 15 , 49 , 57 Stress data during extension demonstrated that the PNP hydrogels containing hydrophilic NPs reached higher stress values with deformation, approaching their yield stresses, but then dramatically failed ( Figure S9 ). In contrast, PNP hydrogels containing hydrophobic NPs gradually dissipate stress well above their yield stress values during elongation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the level of macroscopic consideration, the adaptive performances of intelligent materials are achieved by the autonomous behaviors of molecules or atoms at a nanoscopic level [ 35 ]. When stimuli are introduced, aggregation, rearrangement and directional movement occur among the molecules and atoms [ 36 , 37 ].…”
Section: Classifications and Underlying Mechanisms Of Intelligent Polymersmentioning
confidence: 99%